Curriculum, Community, and Civic Values: A Qualitative Inquiry into Nationalism at Dayah Misbahurrasyad in Aceh - Mulyadi Mulyadi; Nur Balqis; Wasehuddin Wasehuddin; Winda Novianti; Lathifah Hanum (Program Pascasarjana IAIN Langsa, 2025)
This qualitative study examines how Dayah Misbahurrasyad, a modern Islamic boarding school in Aceh Tamiang, integrates religious moderation and nationalism into the student’s education. Using observation, in-depth interviews, and document analysis, the research explores how values such as tolerance, anti-violence, justice, and respect for diversity are embedded through formal curricula, daily routines, and extracurricular activities. Nationalism is reinforced via flag ceremonies, scouting, Red Cross Youth (PMI) programs, and communal work (gotong royong). The study addresses concern about students’ limited grasp of nationalism and challenges stereotypes portraying Islamic boarding schools (dayah) as inherently “anti-nationalist.” Findings reveal that Dayah Misbahurrasyad actively fosters civic values and national identity by merging religious ethics with social practices, such as moderation-themed lessons and community service. This fills an empirical gap in literature that historically emphasizes dayah ’s doctrinal roles (e.g., Zuhdi, 2016) but lacks insight into modern strategies for cultivating inclusive nationalism. By centering santri as active agents in shaping pluralistic identities, the study highlights their role in Indonesia’s democracy. The research offers a replicable model for integrating moderation and nationalism in Islamic education, informing policies to strengthen social cohesion. Challenges, such as uneven student engagement and limited external interaction, underscore the need for innovative approaches to broaden inclusivity.